2014
DOI: 10.1007/s11011-014-9632-2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment with metformin activates Nrf2 antioxidant pathways and inhibits inflammatory responses through induction of AMPK after transient global cerebral ischemia

Abstract: Global cerebral ischemia arises in patients who have a variety of clinical conditions including cardiac arrest, shock and asphyxia. In spite of advances in understanding of the brain ischemia and stroke etiology, therapeutic approaches to improve ischemic injury still remain limited. It has been established that metformin can attenuate cell death in cerebral ischemia. One of the main functions of metformin is proposed to be conducted via AMP-activated protein kinase (AMPK)-dependent pathway in the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(146 citation statements)
references
References 59 publications
(58 reference statements)
7
138
0
1
Order By: Relevance
“…We clearly showed that metformin upregulated the Nrf2 system, while LPS treatment downregulated the Nrf2 system in both HFD-fed mice and HepG2 cells ( Figure 3C and 3D, Supplementary Figure 2 and 3). These results are in line with previous reports showing the interactions of the effects of metformin and LPS on the Nrf2 system [34,35] . The underlying regulatory mechanisms of LPS on the Nrf2 system were not addressed in the current study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We clearly showed that metformin upregulated the Nrf2 system, while LPS treatment downregulated the Nrf2 system in both HFD-fed mice and HepG2 cells ( Figure 3C and 3D, Supplementary Figure 2 and 3). These results are in line with previous reports showing the interactions of the effects of metformin and LPS on the Nrf2 system [34,35] . The underlying regulatory mechanisms of LPS on the Nrf2 system were not addressed in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…There is also a report showing that PTEN promotes Nrf2 phosphorylation-dependent degradation [34] , and therefore, LPS could promote Nrf2 degradation by upregulating PTEN expression. Interestingly, metformin has been shown to inhibit LPS-evoked inflammatory signaling through regulating ATF-3 [38,39] and has been recently found to activate Nrf2 to inhibit the inflammation response [35] . Whatever the specific mechanism involved, our data suggest that LPS-triggered Nrf2 dysfunction and the loss of redox balance could contribute to its detrimental effect on metformin and insulin action.…”
Section: Discussionmentioning
confidence: 99%
“…Recent animal studies have further demonstrated that long‐term metformin pretreatment can obviously alleviate the damage of ischemic stroke to brain tissue 12, 13, 14. In addition, metformin is also effective in treating global cerebral ischemia,15 intracerebral hemorrhage,16 epilepsy,17 Parkinson disease,18, 19 and Huntington disease 20. However, whether and how metformin treatment is effective in reducing brain injury after CA remain uninvestigated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, chronic metformin treatment significantly reduces infarct size in animal model [44]. The mechanism beyond that is chronic metformin therapy down-regulate AMPK in cerebral vessels and decreases lactate accumulation during ischemia [42][43][44][45]. However, acute metformin treatment during ischemic stroke may cause activation of AMPK which has harmful effects on neurons during ischemia with accumulation of lactate [44].…”
Section: Discussionmentioning
confidence: 99%